A Dual‐Function Electrospun Matrix for the Prevention of Herpes Simplex Virus‐1 Infections after Corneal Transplantation. Issue 3 (27th January 2023) - Rohde, Felix; Walther, Marcel; Baur, Florentin; Windbergs, Maike
Abstract : Tissue transplantations are often associated with severe infections. Cornea replacement as the most frequent transplantation worldwide bears the risk of keratitis caused by herpes simplex virus (HSV), posing a severe and sight‐threatening complication. To overcome the current lack of effective HSV therapy in the eye, biodegradable nanofibrous scaffolds incorporating acyclovir (ACV) intended for transplantation along with the cornea graft to prevent viral infections are designed. The rational development of these matrices reveals the strong dependency of the surface wettability on the release kinetics of the tested biocompatible poly(lactic ‐co ‐glycolic acid) (PLGA) polymers. Using a mixture of two PLGA polymers, a tailor‐made release of the antiviral active ACV is achieved for the intended treatment period. In a human in vitro HSV infection model, a synergistic viral inhibition mechanism by binding the virus particles on the fibers surface, while simultaneously releasing the antiviral active, could be confirmed. Besides the controlled ACV release, the polymer fibers bind virus particles to their surface, significantly reducing the virus titer. Based on this tunable dual effect, the fiber scaffolds exhibit a promising antiviral drug delivery platform, which can overcome the limitations of current infection therapy associated with cornea transplantation. Abstract : Rationally developed biocompatible and biodegradable electrospun nanofibers exhibit a synergistic viral inhibition mechanism by binding virus particles on the fiber surface and simultaneously releasing an antiviral agent for a prolonged time period significantly reducing the virus particle burden and thus the severity of viral infections affecting the eye after corneal transplantation.